Reflection and refraction of plane waves at the interface of an elastic solid half-space and a thermoelastic diffusive solid half-space - Kumar, R.; Kansal, T. (Archives of Mechanics, 2012)
The problem of reflection and refraction phenomenon due to longitudinal and transverse waves incident obliquely at a plane interface between uniform elastic solid half-space and thermoelastic diffusive solid half-space has been studied. It is found that the amplitude ratios of various reflected and refracted waves are functions of angle of incidence, frequency of incident wave and are influenced by the elastic properties of media. The expressions of amplitude ratios and energy ratios are obtained in closed form. The amplitude ratios and energy ratios have been computed numerically for a particular model. The variations of energy ratios with angle of incidence are shown graphically. The conservation of energy across the interface is verified. Some particular cases are also discussed.